2015
DOI: 10.4137/bbi.s23773
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing of miRNAs Reveals a Tissue Signature in Gastric Cancer and Suggests Novel Potential Biomarkers

Abstract: Gastric cancer has a high incidence and mortality rate worldwide; however, the use of biomarkers for its clinical diagnosis remains limited. The microRNAs (miRNAs) are biomarkers with the potential to identify the risk and prognosis as well as therapeutic targets. We performed the ultradeep miRnomes sequencing of gastric adenocarcinoma and gastric antrum without tumor samples. We observed that a small set of those samples were responsible for approximately 80% of the total miRNAs expression, which might repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…It was demonstrated that hsa‐miR‐135b is up‐regulated in stomach carcinoma tissues . Based on the results obtained in several studies, hsa‐miR‐135b is reported as a potential biomarker of the intestinal‐type of STAD . In our study, hsa‐miR‐196b and hsa‐miR‐135b were also up‐regulated, which was in line with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…It was demonstrated that hsa‐miR‐135b is up‐regulated in stomach carcinoma tissues . Based on the results obtained in several studies, hsa‐miR‐135b is reported as a potential biomarker of the intestinal‐type of STAD . In our study, hsa‐miR‐196b and hsa‐miR‐135b were also up‐regulated, which was in line with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…MicroRNAs (miRNAs) are small non-coding regulatory RNAs (~23 nucleotides in length) that play a crucial role in the post-transcriptional regulation of gene expression by suppressing target mRNA translation by binding to its 3'untranslated region (UTR) region (10)(11)(12). Therefore, miRNAs can regulate multiple mRNAs to create a complex regulatory network of signaling pathways including oncogene pathways and tumor suppressor pathways, such as the Wnt and PI3K pathways (13)(14)(15)(16).…”
Section: Abnormal Expression Of Mir-135b-5p In Bone Tissue Of Patientmentioning
confidence: 99%
“…In order to find more sensitive biomarkers, we focused on 10 miRs with the highest alteration levels in the tissue of UCB patients (Figure 3). Of these 10 miRNAs, we chose 9 miRNAs, hsa-miR-99a-5p, hsa-miR-100-5p, hsa-miR-125b-5p, hsa-miR-145-5p, hsa-miR-4324, hsa-miR-34b-5p, hsa-miR-29c-3p, hsa-miR-135a-3p, and hsa-miR-33b-3p which were previously reported to have an oncogenic or antioncogenic roles [5,[14][15][16][17][18][19][20][21], (Figure 4). Our previous studies found that the expression levels of antitumorigenic miR-145 were significantly lower in surgically resected BC samples and BC cell lines compared to those in normal bladder tissues, thereby miR-145 decreases the Warburg effect by silencing KLF4 [22,23].…”
Section: Disease Markersmentioning
confidence: 99%